Management of Hyperprolactinemia Caused by Pituitary Microadenoma - Muttaqin, Ibnu; Yuad, Haviz (Andalas Obstetrics And Gynecology Journal, 2024)
Hyperprolactinemia is an increase in fasting levels of the hormone prolactin above 20 ng/ml in men and above 25 ng/ml in women. Hyperprolactinemia occurs more often in women of reproductive age, with a percentage of 9 – 17%. The etiology of hyperprolactinemia can occur due to abnormal pituitary secretions, systemic disease, use of drugs, damage to the hypothalamus-pituitary axis. A 33-year old female patient came to the FER Polyclinic at M. Djamil Hospital with complaints of not menstruating for the past 2 months. Irregular menstruation since 15 years ago, menstruation 2-3 times in 6 months, irregular cycle for 7-8 days. The patient also complained of a fluid like breast milk coming out of the breast for 5 years, initially the fluid came out in a trickle and then gradually reduced and now the fluid comes out occasionally if the breast is squeezed. From the supporting examinations carried out, it was found that the prolactin hormone level in this patient was 134.53, and the results of the MRI examination showed a mass measuring 1.05x1.12x0.5 mm, which was diagnosed as secondary amenorrhea, hyperprolactinemia, and suspected pituitary microadenoma. The patient will be monitored for general condition and vital signs, as well as consultations with colleagues involved, such as consultations to the Internal Medicine section, Endocrinology, Metabolic and Diabetes Subdivision.